Project Planning and Implementation in Niegria: Revisiting International Best Practices - Nick Ngozi Igwe; Anthony Obiora Ude (European Scientific Journal, ESJ, 2018)
The existence of poor project planning and implementation culture is an anti-thesis to development. This is because the growth of any nation is essentially dependent on successful execution of critical development projectsand infrastructures. The purpose of thispaper is to explore the current issues around project planning and implementation in Nigeria’s public sector vis-à-vis international best practices. The methodology adopted was a documentary review of past and current literature which enhance critical and contextual analysis of project implementation and execution culture in the country. It was found that the three tiers of government have not really planned, implemented and executed projects with due diligence in accordance with global best practices. Thus there exists a widespread institutional mediocrity in project execution, deficiency of vision, and inadequate budgetary allocations leading to high cost of project financing and corruption in the long run. The paper recommends amongst other things the establishment of National Public Projects Implementation System (NPPIS),public projects governance institutional framework and project management offices (PMOs), in Ministries Departments and Agencies to support processes for better public projects delivery system.